Clinical and cost effectiveness of a corticosteroid injection versus exercise therapy for shoulder pain in general practice: protocol for a randomised controlled trial (SIX Study). Issue 3 (30th March 2021) - van Doorn, Pieter F; de Schepper, Evelien I T; Schiphof, Dieuwke; Ottenheijm, Ramon P G; Thoomes-de Graaf, Marloes; Koopmanschap, Marc A; van Ochten, John M; van der Windt, Danielle A; Bindels, Patrick J E; Koes, Bart W; Runhaar, Jos
Abstract : Introduction: Shoulder pain is common and the prognosis is often unfavourable. Dutch guidelines on the treatment of shoulder pain in primary care recommend a corticosteroid injection or a referral to exercise therapy, if initial pain management fails and pain persists. However, evidence of the effectiveness of a corticosteroid injection compared with exercise therapy, especially in the long term, is limited. This trial will assess the clinical effectiveness and cost effectiveness of a corticosteroid injection compared with physiotherapist-led exercise therapy over 12 months follow-up in patients with shoulder pain in primary care. Methods and analysis: The SIX Study is a multicentre, pragmatic randomised clinical trial in primary care. A total of 213 patients with shoulder pain, aged ≥18 years presenting in general practice will be included. Patients will be randomised (1:1) into two groups: a corticosteroid injection or 12 sessions of physiotherapist-led exercise therapy. The effect of the allocated treatment will be assessed through questionnaires at 6 weeks and after 3, 6, 9 and 12 months. The primary outcome is patient's reported shoulder pain-intensity and function, measured with the Shoulder Pain and Disability Index, over 12 months follow-up. Secondary outcomes include cost effectiveness, pain-intensity, function, health-related quality of life, sleep quality, patient's global perceived effect, work absence, healthcare utilisation and adverse events. Between group differences will be evaluated using a repeated measurements analysis with linear effects models. A cost-utility analysis will be performed to assess the cost effectiveness using quality-adjusted life years from a medical and societal perspective. Ethics and dissemination: This study was approved by the Medical Ethics Committee of Erasmus MC University Medical Center Rotterdam (MEC 2020-0300). All participants will give written informed consent prior to data collection. The results from this study will be disseminated in international journals and implemented in the primary care guidelines on shoulder pain. Trial registration number: Dutch Trial Registry (NL8854).